THE USE OF NATURAL TRASS FROM SAYUTAN MAGETAN AND LIME FROM NGAMPEL BLORA AS THE MATERIAL OF CEMENT SUBSTITUTION FOR MORTAR MIXTURE - Muhammad Nurzain; Iman Satyarno; Muslikh Muslikh (Journal of the Civil Engineering Forum, 2013)
Construction works in the Regency of Magetan, as well as in the mountain area far from capital cities and remote from transportation facilities, require large amount of material. In order to cope with the need of sand, people uses natural trass which are plenty to be found in the area. Test and research on its characteristic and strength with its potentials to be used as cement substitution have never been carried out. Lime was taken from Ngampel village, Blora as it is commonly sold in the area. The planned mixture of lime-trass paste was in the effort to obtain the best composition. The weight ratios used were 100%:0%, 80%:20%, 60%:40%, 40%:60%, 20%:80 and 0%:100%. The mortar mixture with cement substitution was 100%, 80%, 60%, 40%, 20% and 0%.The compressive strength of the lime-trash mixture was between 0.000 MPa and 2.545 MPa. The mortar compressive strength achieved was 0.373 MPa - 26.585 MPa. The test results of mortar compressive strength showed that the more cement substitution amount used, the less the compressive strength would be. The mortar compressive strength increased in line to the age of the mortar. The mortar tensile strength obtained was 0.000 MPa - 2.169 MPa. The block compressive strength obtained was 3.336 MPa - 3.403 MPa. Water absorbency of the block was 15.831% -16.056%.